Identification of Potential Immune-related Biomarkers in Gastrointestinal Cancers - Zhu, Tianyu; Dai, Qi; He, Ping-An (Current Bioinformatics, 2021)
Objectives: Gastrointestinal (GI) cancer is the most common and lethal malignant tumor, while limited research and biomarkers are available to stratify patients who are likely to benefit from immunotherapy in GI cancers. During early diagnosis and prognosis of GI cancers, searching for shared potential biomarkers and differences among stages is an urgent and challenging task. The staging RNA expression data corresponding to immune genes were analyzed to infer the immune system in each stage of GI cancers. Methods: The differential expression gene analysis was performed to analyze the expression of 758 immune genes between normal and each stage samples of GI cancers. Enrichment analysis including GO and KEGG pathway analysis was carried out to investigate the role of these differential genes and underlying mechanisms in GI cancers. Furthermore, PPI network analysis recognized the hub genes among these DEGs. Overall survival analysis was processed to clarify the diagnostic and prognostic role of these potential biomarkers in early and advanced stages. Results: Our present work revealed the immunological commonness and differences across stages of GI cancers, and disclosed several potential immune-related biomarkers, including CCL20, C7, CD36, CXCL11, and CLEC5A. The potential biological function which immune system participates across the GI cancers was highly correlated with virus and membrane. Conclusion: Our result facilitates to understand the involvement of immune system in GI cancers and better design treatment strategies based on current cancer immunotherapy.
Keywords: survival